Pengaruh Pendidikan Kesehatan Terhadap Kecemasan Primigravida Trimester III - Vitria Komala Sari; Wiwik Kusumawati; Herlin Fitriana (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
The purpose of this study is to describe the anxiety levels in primigravida in the face of deliveries at the health center of Bukittinggi. This type of research is experimental with pre-experimental design using a one-group pretest-posttest with consecutive sampling technique. Data collection techniques used questionnaires anxiety level of the Zung Self Rating Anxiety Scale. Results of the study showed a mean value of bivariate analysis on a pregnant woman before being given health education (pretest) = and the mean value after a given health (posttest) = which shows the p value = 0,000 which means there is the influence of health education on anxiety primigravida.